Revisiting Integrated Coastal and Marine Management in Canada: Opportunities in the Bay of Fundy - Eger, Sondra L.; Stephenson, Robert L.; Armitage, Derek; Flannery, Wesley; Courtenay, Simon C. (Frontiers in Marine Science, 2021)
Limited progress has been made in implementing integrated coastal and marine management (ICM) policies globally. A renewed commitment to ICM in Canada offers an opportunity to implement lessons from previous efforts over the past 20 years. This study applies three core ICM characteristics identified from the literature (formal structures; meaningful inclusion; and, innovative mechanisms) to identify opportunities for operationalizing ICM from participants’ lived experiences in Atlantic Canada. These characteristics are employed to assess and compare ICM initiatives across two case studies in the Upper Bay and the Lower Bay of Fundy. The assessments are based on semi-structured interviews conducted with key participants and a supplementary document analysis. The following insights for future ICM policies were identified: adaptive formal structures are required for avoiding previous mistakes; a spectrum of approaches will support meaningful engagement in ICM; local capacity is needed for effective innovative mechanisms; and, policy recommendations should be implemented in parallel. Although these insights are relevant to each of the two sub-regional case studies, the paths taken to incorporating and realizing them appear to be location-specific. To account for these site-specific differences, we suggest more attention be given to strategies that incorporate local history, unique capacity of actor groups and location-specific social-ecological systems objectives. We provide the following recommendations on policy instruments to assist in moving toward enhanced regional ICM in the Bay of Fundy, and that may also be transferable to international ICM efforts: update policy statements to incorporate lessons from previous experiences; strengthen commitment to ICM in Federal law; create a regional engagement strategy to enhance involvement of local actor groups; and, enhance the role of municipal governments to support local capacity building and appropriate engagement of local actors in ICM processes.